Analisis Kritik Sosial Berbasis Postkolonialisme dalam Puisi Sajak Sebatang Lisong Karya W.S. Rendra - Nasya Nabila Said; Ratna Lolane Sianipar; Stella Parta Siagian; Stevani Situmorang; Erfanintia Siringoringo; Jesicha Nainggolan; Fitriani Lubis (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the poem Sajak Sebatang Lisong by W.S. Rendra through a postcolonial lens, focusing on the underlying social criticism embedded within the text. The poem reflects the persistent social inequalities that continue to affect Indonesian society in the post-independence era, particularly in the realms of education and the marginalization of impoverished children. Through symbols such as the cigarette (lisong), wealthy elites (cukong), and the imagery of an endless road, the poem highlights the lingering presence of colonial structures within contemporary social and educational systems. Employing a qualitative descriptive approach, the study utilizes textual analysis and socio-cultural context as primary analytical tools. The findings reveal that political independence has not been fully accompanied by social justice. Structural oppression and limited opportunities continue to hinder the younger generation in their pursuit of a better future. As such, the poem serves as a powerful literary critique of neocolonial practices and ongoing social alienation. These findings contribute to a deeper understanding of how literature can reflect colonial legacies and the socio-political dynamics of post-independence Indonesia, while also enriching the discourse in postcolonial literary studies.